2017
DOI: 10.1093/fampra/cmw133
|View full text |Cite
|
Sign up to set email alerts
|

Health reforms in china: the public’s choices for first-contact care in urban areas

Abstract: Purpose. To examine the public's views towards their choice of first-contact care and its associated factors in urban China. Methods. A mixed-method study was adopted using individual interviews, focus group interviews and a cross-sectional survey. The study was conducted among the general public between September 2014 and September 2015 in Zhejiang province, China. Results. Six focus groups and 13 individual interviews were conducted. The questionnaire was completed by 1248 respondents with a response rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 19 publications
4
64
0
Order By: Relevance
“…This analysis illustrating significant heterogeneity in the quality in GP training approaches helps explain in part why GPs face a significant challenge for earning the public's trust. 7,33,36,37 We agree with Wu, et al, 7 on the need to build on positive public perceptions about primary care providers' value as a trusted source for referral, drug dispensing, managing chronic diseases, and providing patient education. Trainees may benefit from discussion on how to advocate their skills as providers SPECIAL ARTICLE of choice for first-contact care to patients.…”
Section: Overcoming Lack Of Trustmentioning
confidence: 77%
“…This analysis illustrating significant heterogeneity in the quality in GP training approaches helps explain in part why GPs face a significant challenge for earning the public's trust. 7,33,36,37 We agree with Wu, et al, 7 on the need to build on positive public perceptions about primary care providers' value as a trusted source for referral, drug dispensing, managing chronic diseases, and providing patient education. Trainees may benefit from discussion on how to advocate their skills as providers SPECIAL ARTICLE of choice for first-contact care to patients.…”
Section: Overcoming Lack Of Trustmentioning
confidence: 77%
“…Variables were chosen based on availability in questionnaires, the Andersen Health Service Utilization Model and their associations with choices of first‐contact care shown by previous studies…”
Section: Methodsmentioning
confidence: 99%
“…Their choices of first‐contact care would play an important role in taking full advantage of medical resources, which should be paid more attention to. Previous researchers found that there were complex relationships between factors and healthcare utilization preferences . Although most of the previous studies focused on all age groups and used descriptive statistics or regression models, which could not clearly show direct and indirect pathways from factors to older adults’ choices of first‐contact care.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations